2019
DOI: 10.1002/adom.201900043
|View full text |Cite
|
Sign up to set email alerts
|

Optimized White Reflectance in Photonic‐Network Structures

Abstract: freedom to tune light transport properties in these media. Indeed, shapes such as prolate ellipsoids or cylinders can be packed up to higher densities delaying the onset of spatial correlations at the cost of increased angular correlations. [10][11][12] Interestingly, both these aspects-namely, the high density and prevalent orientation exhibited by packed rods-can contribute to increase the overall turbidity, which makes cylinders particularly suited to realize highly turbid materials with a flat response ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Therefore, their appearance results from the interplay between: 1) the single-scatterer properties as the scattering cross-section; 2) the ensemble properties as the filling fraction (i.e., the volume percentage occupied by the scatterers), the average orientation of the scatterers, and the structure factor (i.e., the spatial organization of the scatterers). [6,7] The appearance of a disordered material (which is defined as system where the structure factor does not exhibit longrange order) is directly determined by the optical thickness (OT). This parameter is defined as the ratio between the physical thickness of a medium and the transport mean free path, that is, the average distance over which light loses memory of its initial direction.…”
Section: Doi: 101002/adma202001215mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, their appearance results from the interplay between: 1) the single-scatterer properties as the scattering cross-section; 2) the ensemble properties as the filling fraction (i.e., the volume percentage occupied by the scatterers), the average orientation of the scatterers, and the structure factor (i.e., the spatial organization of the scatterers). [6,7] The appearance of a disordered material (which is defined as system where the structure factor does not exhibit longrange order) is directly determined by the optical thickness (OT). This parameter is defined as the ratio between the physical thickness of a medium and the transport mean free path, that is, the average distance over which light loses memory of its initial direction.…”
Section: Doi: 101002/adma202001215mentioning
confidence: 99%
“…Different numerical algorithms have been recently developed to separate these contributions and gain insight into the scattering optimization process. [6,7,28] By exploring a large parameter space for single-particle and ensemble configurations, Jacucci et al demonstrated that optimized ensembles of anisotropic scatterers outperform the scattering efficiency of their isotropic counterpart. [6] In detail, this result is valid when the anisotropic system exhibits an orientational order where the long axis of the scatterers is on average perpendicular to the incoming beam, [6,7] as showcased by the Cyphochilus beetle.…”
Section: Minimized Scattering: Transparency In Naturementioning
confidence: 99%
“…A priori knowledge of the internal structure makes it ideal for studies of light propagation that are sensitive to microscopic wave interference of light. [29] In the literature, several scattering media with deterministic geometry and scattering properties have been demonstrated using different nanofabrication techniques. Matoba et al [30] have created a large-volume deterministic scattering medium with laser micromachining, [31,32] but with undefined scattering strength.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The key parameters to its success are the anisotropic shape, dimensions and highly optimized filling fraction of the chitinous fibrils. 10,11 Recently, several groups attempted the fabrication of scattering networks with low refractive index polymers with performances comparable to the one of the Cyphochilus beetle. In particular, highly scattering material based on fibrillar-like networks were obtained by exploiting phase separation of polymers in a solvent mixture combined with kinetic arrest.…”
mentioning
confidence: 99%
“…The selection of high aspect ratio rods was motivated by biological, 6 and numerical systems 10,11 which showcased the possibility of exploiting anisotropic building blocks for improved scattering efficiency in low refractive index media. It is important to note that the optical response of an ensemble of anisotropic colloids depends both on the single-particles properties (shape and dimensions) and by the structural ones (alignment and filling fraction).…”
mentioning
confidence: 99%